Barriers to technology transfer in medical centres: a contextualised embeddedness perspective. (2015) - Roll, Michal; Lerner, Miri; Gimmon, Eli
The vital sector of medical centres and hospitals remains poorly investigated in the literature on technology transfer (TT). The current article explores the mechanisms adopted and locally generated in medical centres to overcome barriers to TT. A qualitative study was conducted at the six largest medical centres in Israel to identify those barriers to TT as reflected in patent applications. The study was based on an embeddedness theory and on previous studies conducted in academic settings. Our findings indicated that: 1) TT from medical centres is affected by regulation and institutional ownership; 2) assessment of barriers to TT necessitates contextualisation and the consideration of local conditions at each medical centre (e.g., size, research funds, ownership and university affiliation).